My Chief Interest Is Germination: an Interview with Elisa Kay Sparks - Sparks, Elisa Kay; Santos Brigida, Marcela; Sant’Ana Ferreira Mendes, Thales (Palimpsesto - Revista do Programa de Pós-Graduação em Letras da UERJ, 2020)
Elisa Kay Sparks, Professor Emerita of English at Clemson University, has established a career that is a source of inspiration to any scholar in the Humanities. Having taught Literature and Women’s Studies for 35 years at Clemson, she is part of the history of entire generations of students. Furthermore, Professor Sparks’s research interests and practices put her at an ideal standpoint to discuss the “connections and innovations” element of this number’s theme. She is an international reference in Virginia Woolf and Modernist Studies and one of the Virginia Woolf International Society’s main collaborators. Throughout the years, she has established an impressive body of critical work investigating parks, gardens, and flowers in Woolf’s life and writing. She has also drawn innovative connections between the works of the modernist writer and those of the American painter Georgia O’Keeffe. Taking in the stature of Professor Sparks’s contributions to Woolf Studies specifically and to the Humanities in a broader sense allows us to fully appreciate the reach of her views on the importance of sharing knowledge. For, beyond the fact that Professor Sparks is a prolific researcher, she is a truly generous one. Throughout the years, she has authored numerous blogs sharing her findings with readers and researchers entirely for free. In this interview, it becomes clear that, allied with the rigour of her academic production and her extraordinary career as a teacher, this impulse towards making knowledge and critical thinking as widely available as possible makes Professor Sparks a model of academic practice we should all aspire to.